2012
DOI: 10.1021/jf3017699
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Phenolic Compounds in Table Olives (Olea europaea)

Abstract: The Mediterranean diet appears to be associated with a reduced risk of several chronic diseases including cancer and cardiovascular and Alzheimer's diseases. Olive products (mainly olive oil and table olives) are important components of the Mediterranean diet. Olives contain a range of phenolic compounds; these natural antioxidants may contribute to the prevention of these chronic conditions. Consequently, the consumption of table olives and olive oil continues to increase worldwide by health-conscious consume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
176
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(194 citation statements)
references
References 104 publications
6
176
0
3
Order By: Relevance
“…The enzyme of β-glucosidase is closely related to the oleuropein hydrolysis and the debittering process in table olives so it is a desirable characteristic for a potential starter culture [39].…”
Section: β-Glucosidase Activitymentioning
confidence: 99%
“…The enzyme of β-glucosidase is closely related to the oleuropein hydrolysis and the debittering process in table olives so it is a desirable characteristic for a potential starter culture [39].…”
Section: β-Glucosidase Activitymentioning
confidence: 99%
“…In olive trees, KL affected positively the olive oil quality and composition, in terms of total phenols, Reactive oxygen species (ROS), formed as a result of oxidative stress, are known to be responsible for the development of some diseases, targeting lipids, proteins and deoxyribonucleic acid (DNA) in living organisms (Ghanbari et al, 2012). Phenolic compounds in olives can restrict the deleterious effects of ROS, either by their free radical scavenging ability (by donating a hydrogen atom to the ROS, reducing and stabilizing it), or by chelating transition metals, suppressing the oxidative reaction in which them are involved (Charoenprasert and Mitchell, 2012). These phytochemicals also affect the sensorial and aromatic characteristics of both olive fruits and oil and the chemical stability of olive oil (Ghanbari et al, 2012;Servili et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Table olives and olive oil are important components of the Mediterranean diet that provide numerous health benefits and are largely consumed all over the world (Blekas, Vassilakis, Harizanis, Tsimidou, & Boskou, 2002;Cioffi et al, 2010;Owen et al, 2004;Stark & Madar, 2002). In fact, many studies have reported that olive oil may have a role in the prevention of coronary heart disease and cognitive impairment (e.g., Alzheimer's disease) as well as it may have protective effects against cancers of the colon, breast, and ovary; diabetes accompanied by hypertriglyceridemia; and inflammatory and autoimmune diseases such as rheumatoid arthritis (Charoenprasert & Mitchell, 2012;Cicerale, Lucas, & Keast, 2010;Malheiro et al, 2012).…”
Section: Introductionmentioning
confidence: 99%